Margaret Fuller’s Summer on the Lakes, in 1843 and the Condition of America - Newman, Lance (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractIn her travel narrative Summer on the Lakes, in 1843, Margaret Fuller differentiates consistently between the materialistic or utilitarian motivations of settlers, on one hand, and the spiritual or aesthetic aims of tourists on the other. Her trip occurred during the depths of the severe economic crisis of 1837 to 1844, a period of widespread questioning of the historical progressiveness of capitalism. Many among Fuller’s circle of radical bourgeois Bostonians felt that the world had been badly deformed by what they called “the spirit of commerce”, and they worried that New England was developing what Thomas Carlyle diagnosed as the “Condition-of-England.” This romantic assessment of socio-economic pathologies focused on the idea that a materialist, instrumentalist, and rationalist civilization had lost touch with the organic “laws of nature.” Summer on the Lakes, then, is structured by the tension between a vision of a just society rooted in nature and the stark reality of America’s westward expansion, between an abiding faith in the human potential to live up to the beauty of picturesque landscapes and a clear understanding of the cold social calculus of immediate profit.